Experimental study and theoretical analysis on fluidized activation of coal gasification fly ash from an industrial CFB gasifier. (15th February 2023) - Qi, Xiaobin; Yang, Qiyao; Song, Weijian; Zhu, Zhiping; Lyu, Qinggang
Highlights: Fluidized activation of GFA were experimentally and theoretically studied. Fluidized activation of GFA was evaluated by comparing with steam activation results. Fluidized activation developed the pore structure of GFA in a seconds-level time. GFA has natural physical advantages in enhancing diffusion of active agent. Increasing temperature is an effective control method for fluidization activation of GFA. Abstract: The gasification fly ash (GFA), a bulk industrial solid waste from coal gasification process, urgently needs to be effectively disposed. In order to use the GFA as porous carbon materials, fluidized activation experiments of the GFA from an industrial circulating fluidized bed (CFB) gasifier were conducted in a bench-scale CFB test rig, as well as steam activation experiments of GFA in a vertical tube furnace and theoretical analysis on the activation process. Due to the ultrafine particle size, the GFA faces a fluidization problem and auxiliary particles are needed to stabilize its fluidization. In the fluidized activation, the pore structure of GFA particles becomes developed in a seconds-level time (about 1.5 s). The specific surface area ( S BET ) of activated GFA increases with temperature, maximally increasing by 48.9 % and reaching 204 m 2 /g. Steam activation experiments show that the GFA has an activation potential of 362 m 2 /g ( S BET ) and the pore structure evolution of GFA can be quantified by carbon conversion ratio. Based on this, the fluidized activation of GFA is found in the stage of pore development. By appropriately increasing the carbon conversion ratio (below 40 %), the fluidized activation effect of GFA is expected to be improved. Theoretical analysis indicates for the GFA the features of ultra-fine particle size and well-developed pore structure greatly enhance the diffusion rate of active component into the particles. Under the strong diffusion effect, increasing temperature is a critical means to realize the rapid and effective activation of GFA in a finite time.